PENERAPAN PEMBELAJARAN NUMBERED HEADS TOGETHER BERBANTUAN QUESTION AND ANSWER CARD PADA MATERI HIDROKARBON (Universitas Negeri Semarang, 2013)
The aspects that influence the success in education are curriculum, facilities, teachers, students and learning models. This research used Numbered Heads Together (NHT) learning model. The purpose of this research was to determine the effect of the use of NHT learning model to the learning outcomes of chemistry on hydrocarbons subject. The population in this research class are X grader of Senior High School (SHS) in Wonogiri for the academic years 2011/2012. The technique for determining the sample used the cluster random sampling technique. To find out the influence of the use of media-assisted learning model NHT Question and Answer Card used test two mean difference (t test). Based on the analytical results obtained t count equal 3.794 and 2.0017 for t table at the level of error of 5% and dk = 58. So the t count t table which mean that there is a significant difference namely the average of chemistry learning outcomes in the experiments class is better than the control class. Biserial correlation coefficient test showed biserial coefficient of 0.548. It can be concluded that the Numbered Heads Together learning model with Question and Answer Cards give the significant affects to the chemistry learning outcomes in of hydrocarbons subject with contributian as 29.99%.Key Words : Numbered Heads Together learning